Constraints faced by farmers and processors in farmed shrimp value chain in Gujarat - Kumar, Nalini Ranjan; Navghan, Mahida (Indian Farming, 2018)
Shrimp farming is highly profitable venture in the state and both the farmers and processors are earning substantial profit and contributing to the value as per their contribution in the cost. In spite of good profit, actors are facing above mentioned constraints in improving value at their stage. Addressing those constraints will help in improving the functioning of farmed shrimp value chain which will ultimately improve the value addition and competitiveness of shrimp in international market.